Control Químico de prodiplois longifila gagne en solanum lycopersicum l. en el hibrido kattia en Consultora Costa Verde S.A.C. – Chepen – La Libertad - Arteaga Leyva, Marcelo (2017)
The objective of the present work was to determine the chemical control of Prodiplosis longifila Gagne in Solanum lycopersicum L. HIBRIDO KATTIO EN Consultora Costa Verde S.A.C. - Chepén - La Libertad. The monitoring was evaluated and randomly selected weekly, 70 tomato plants per hectare were taken, determined: the number of larvae per flower buds, number of adults per plant. For the chemical control of Prodiplosis longifila Gagné, which were applied to the transplant insecticides as: Imidacloprid (Fortagen 350 SC) with doses of 1 liter / ha, Movento (spirotetramat) with doses of 600 ml / ha, in which it was determined that a good chemical control of Prodiplosis longifila Gagné was carried out.